EFEKTIVITAS PEMBINAAN REINTEGRASI SOSIAL BERBASIS CINTA TANAH AIR UNTUK PENCEGAHAN RESIDIVISME STUDI KASUS LPP KELAS IIA BANDUNG - Feni Verawati; Dasim Budimansyah; Dwi Iman Muthaqin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the effectiveness of a Love of Country (Cinta Tanah Air)-based social reintegration coaching model in reducing the risk of recidivism among female inmates at the Class IIA Women's Correctional Institution in Bandung, Indonesia. Female inmates face multiple vulnerabilities, including social stigma, economic marginalization, and gender-based discrimination, which increase their risk of reoffending. Employing a qualitative case study approach grounded in Creswell's constructivist and transformative worldviews, data were collected through semi-structured interviews with the Head of Inmate Guidance Section, a correctional officer, and three female inmates, complemented by participatory observation and analysis of the Inmate Coaching Assessment System (SPPN) data from January–April 2026. The findings indicate that the coaching model, which combines personality development programs (civic awareness, religious activities, flag ceremonies, and scouting) with vocational training (sewing, horticulture, language learning, and barista skills), contributes to positive behavioral transformation. SPPN records show consistently high performance, with scores of 86.5–86.6% in personality development, 85.6% in independence, 96.0–96.1% in attitude, and 99.5% in mental health. The institutional recidivism rate was recorded at 12.3% (51 of 413 inmates). Analysis using Lickona's Character Formation Theory, Desistance Theory, Civic Sensibility, Feminist Legal Theory, and Labelling Theory reveals that while civic disposition is successfully cultivated within the institution, its translation into sustainable civic action after release remains constrained by social stigma, economic challenges, and limited post-release support. The study recommends integrating gender-responsive programs, economic empowerment initiatives, and community destigmatization efforts to strengthen long-term recidivism prevention